Unpacking the Resource–Value–Performance Nexus in SMEs - Sanawiri, Brillyanes; N, Anjar Septian; Sadewo, Satrio Tegar (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study investigates how resource leverage and value creation interact to influence the overall performance of SMEs within an entrepreneurial marketing framework. It addresses the gap in understanding whether leveraging limited resources translates into performance gains when mediated by value creation.Methodology: A quantitative research design was employed, utilizing a structured questionnaire distributed to 140 SME owners and managers. Data from these respondents were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the measurement and structural models linking resource leverage, value creation, and performance.Findings: The results show that resource leverage has a significant direct effect on SME performance (β = 0.333, p = 0.000). Additionally, resource leverage strongly influences value creation (β = 0.604, p = 0.000), which in turn has a substantial effect on SME performance (β = 0.527, p = 0.000). The mediation analysis confirms that value creation significantly mediates the relationship between resource leverage and SME performance (β = 0.319, p = 0.000), indicating that firms that effectively transform financial, human, and social resources into customer-oriented value offerings achieve superior outcomes—such as higher financial returns, customer loyalty, and market differentiation.Conclusion: This study confirms the importance of value creation in maximizing the impact of resource leverage. It contributes to entrepreneurial marketing and resource-based view literature by highlighting the strategic role of co-creation, innovation, and market responsiveness in enhancing SME performance, particularly in resource-constrained environments.